A two-step method for rate-dependent nano-indentation of hydrogels. (14th February 2018) - Simič, Rok; Mathis, Christian H.; Spencer, Nicholas D.
Abstract: Soft, biphasic materials such as hydrogels are commonly used to mimic lubrication and confinement mechanics of biological tissue such as articular cartilage or the cornea. In-depth understanding of such mechanics is crucial for designing synthetic replacements for cartilage, contact-lens materials or soft coatings for medical devices. Using colloidal-probe atomic force microscopy (AFM), surfaces can be investigated at the nanoscale and information on the contact modulus, poro-viscoelastic properties and the permeability can be extracted. Yet, probing the surface of a soft material in a liquid environment is challenging, since the point of contact between a probe and sample surface during finite-rate indentation can be obscured by viscous squeeze-out effects of temporarily confined liquid. To address this issue, we have developed a 2-step indentation method that enables accurate alignment of finite-rate indentation curves with respect to the contact point of quasi-static indentation of soft matter in liquid. In this work, the issue and the method are illustrated by measurements on a commonly used poly(acrylamide) (PAAm) hydrogel. We have shown that liquid squeeze-out may cause non-negligible force offsets that can result in false contact-point determination during finite-rate indentation. The presented method allows accurate alignment of the indentation curves, enables one to accurately study the rate-dependent contact moduli and related stiffening effects, and thus greatly facilitates mechanical characterization of both biological as well as synthetic soft materials. Graphical abstract: Image 1 Highlights: Indentation is an essential method for probing mechanical properties of hydrogels. The point of contact during indentation in liquid is hidden by fluid squeeze-out. Surface roughness, slip and permeation hamper the prediction of squeeze-out effects. With the 2-step indentation method squeeze-out can be ignored and the curves aligned. The method enables the accurate determination of rate-dependent stiffening effects.